EFEKTIVITAS PELAKSANAAN PROGRAM INVENTARISASI PENGUASAAN, PEMILIKAN, PENGGUNAAN DAN PEMANFAATAN TANAH (IP4T) GUNA MENINGKATKAN PELAYANAN DI KANTOR PERTANAHAN KABUPATEN AGAM - Yoni Yulia Putri; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
Abstract This study aims to describe how the IP4T program is implemented to improve services at the Agam District Land Office. This research uses descriptive qualitative methods. Research informants were determined purposively, namely Kasi Penahan Pertanahan, IP4T committee members, nagari officers, and the community. The data sources in this study consist of two, namely primary and secondary data. The data collection technique of this study consisted of observation, interviews and documentation. The results of the study show how the implementation of the IP4T program to improve services at the Agam Regency Land Office is still not effective, because planning and implementation is still needed in the program. Keywords: Effectiveness, Land Administration, Public Policy, Public Service, IP4T Program.